Letter to candidates from Mary Ellen Bush, President of the California Pro-Life Council - Mary Ellen Bush:::::: (1976)
This letter, dated April 2, 1976, is from the California Pro-Life Council to candidates for federal and state legislative office. It explains that the organization is gathering information on candidates' positions regarding abortion, which it describes as a major political and social issue. The council requests that candidates complete and return an enclosed questionnaire by April 22, noting that responses will be a key factor in preparing candidate profiles distributed through local affiliates. The questionnaire focuses on support for a proposed Human Life Amendment to the U.S. Constitution to restore what the group describes as the right to life. The letter is signed by Mary Ellen Bush, President, and includes a brochure and reprint for additional information.